BLENDING OLD AND NEW, THRIVING LOCALLY TOGETHER- A PROPOSAL OF BOT PROJECT OF TAINAN ANCIENT FISH MARKET - Chih Wang, Chien; Tsai Lu, Te; Chun Chiu, Hui (International Journal of Application on Economics and Business, 2025)
The present study uses the Tainan Old Fish Market BOT (Build-Operate-Transfer) project as a case study to explore how traditional and modern elements can be integrated. Through the processes and planning outcomes of local participation and co-prosperity mechanisms, this research provides a reference proposal case for promoting the revitalization of historic buildings through blending old and new as well as thriving locally together.This study adopts literature analysis and case investigation to thoroughly examine the planning, design, operation, and benefit evaluation of the Old Fish Market BOT project, presenting a comprehensive overview of a BOT project. The findings indicate that the key to the BOT model lies in sound regulatory design, collaboration among diverse stakeholders, and a high degree of community participation. In this case, civic movements and local opinions were incorporated during the design phase, preserving the original building structure while integrating multiple functions such as accommodation, cultural and creative industries, and dining. Furthermore, the project created spaces with local characteristics, including historical tours, markets, and public art, thereby realizing blending old and new and thriving locally together.In terms of operation and management, the project adopted a cross-type accommodation business model, emphasizing, brand building, service innovation, and local talent cultivation, while establishing diversified revenue models and risk management mechanisms. The revitalization of historic buildings not only preserves cultural memory but also stimulates tourism, industrial upgrading, and the local economy, thereby enhancing urban competitiveness and residents' sense of identity. The present study summarizes key strategies for promoting the reuse of historic buildings, including the improvement of regulations, strengthening community participation, fostering public-private collaboration, and introducing sustainable development concepts. Specific recommendations are provided for the government, enterprises, and communities. Although this case was not the final winning proposal for the BOT project, its contribution lies in providing a model for historic building revitalization, deepening the reference for blending old and new and thriving locally together, and offering policy and practical insights for cultural heritage preservation and local revitalization in Taiwan and other regions.